Margin Pemasaran Rantai Pasok Sayuran Kangkung di Griya Hijau Hidroponik - Muharam, Fauzan Emeraldi Rena; Syamsiyah, Nur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
ABSTRACT Agriculture is a crucial sector for the livelihood of the Indonesian population, contributing significantly to the Gross Domestic Product (GDP) with a contribution of 12.40% in 2022. Horticulture, including vegetables, plays a role in improving community nutrition and serves as a source of economic enhancement for producers. This research aims to analyze the marketing margin of kangkung vegetables at Griya Hijau Hydroponics. The results show that the marketing margin received by Griya Hijau Hydroponics varies depending on the marketing channel. In Marketing Channel I, the margin received is Rp 1,675 per kilogram from sales to restaurants. In Marketing Channel II, the margin received is Rp 25,190 per kilogram from sales to supermarkets. In Marketing Channel III, the margin received is Rp 8,600 per kilogram from direct sales to consumers. This indicates that the choice of marketing channel greatly affects the profits obtained.